Survei ketersediaan sarana dan prasarana Sekolah Renang Lumbaloomba di Shah Alam Malaysia. (Indonesian Journal for Physical Education and Sport, 2021)
Siti Nadia Sarfah. Survey of the Availability of Facilities and Infrastructure for the Lumbaloomba Swimming School in Shah Alam Malaysia 2019. Thesis, Department of Physical Education, Health and Recreation, Faculty of Sport Science, State University of Semarang, Supervisor Lulu April Farida, S.Pd, M. Pd. The learning objectives amd the sports achievement cannot be separated from adequate physical education facilities and infrastructure in accordance with sports standards. In physical education there is aquatic learning which consists of water introduction, swimming styles, and safety in water. This study uses a quantitative research approach. Data using observation, interviews and documentation. Data analysis using descriptive analysis. The research location is at the Lumbaloomba Swimming School, Syah Alam Malaysia. Respondents in this study were facilities and infrastructure for the Lumbaloomba Swimming School, Syah Alam Malaysia. The results of the study explained that: (1) The facilities and infrastructure of the Lumbaloomba Swimming School, Syah Alam Malaysia seen from the availability, had fulfilled the overall learning at the Lumbaloomba Swimming School, Syah Alam Malaysia. (2) The facilities and infrastructure of the Lumbaloomba Swimming School, Syah Alam Malaysian are seen from the conditions that have met the overall learning conditions at the Lumbaloomba Syah Alam Swimming School Malaysia. It can be concluded that in the Lumba Lumba Swimming School, school facilities and infrastructure have met the standards of the FINA and Permendikbud. seen from the 7 owned infrastructure such as: (1) swimming pool (2) reception room (3) waiting room (4) changing room (5) control room (6) staff room and (7) warehouse and the condition of the facilities in it. And with the procedures for using the facilities before learning and after learning at school. Lumbaloomba Swimming School provides learning media to make it easier for educators to carry out the learning process.